2010
DOI: 10.4293/108680810x12674612014987
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral Injury Due to a Harmonic Scalpel During Laparoscopic Salpingo-oophorectomy

Abstract: This report highlights the need for vigilance when using laparoscopic energy sources and suggests surgeons who use the Harmonic scalpel pay close attention to application times during tissue dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…There are various reports of successful laparoscopic procedures using ultrasonic energy devices. This includes gynecological [45–48], laparoscopic cholecystectomy [4951], laparoscopic appendectomy [52], laparoscopic myomectomy [53, 54], laparoscopic colorectal [55], laparoscopic salpingo-oophorectomy [56] and laparoscopic management of cornual heterotopic pregnancy [57]. Ultrasonic scalpel (Harmonic ACE) was also successfully used in division of pulmonary vessels in video assisted lung resection [58].…”
Section: Methodsmentioning
confidence: 99%
“…There are various reports of successful laparoscopic procedures using ultrasonic energy devices. This includes gynecological [45–48], laparoscopic cholecystectomy [4951], laparoscopic appendectomy [52], laparoscopic myomectomy [53, 54], laparoscopic colorectal [55], laparoscopic salpingo-oophorectomy [56] and laparoscopic management of cornual heterotopic pregnancy [57]. Ultrasonic scalpel (Harmonic ACE) was also successfully used in division of pulmonary vessels in video assisted lung resection [58].…”
Section: Methodsmentioning
confidence: 99%
“…Another possible mechanism is that the appendiceal artery was indirectly affected by secondary thermal injury during harmonic dissection of the mesenteric lesion. Whilst uncommon, unexpected thermal injuries to surrounding structures have been reported during use of Harmonic dissection 7 .…”
Section: Discussionmentioning
confidence: 99%
“…This vapor may have dissected tissue planes and traveled to the ureter. 5 Prior ureteric catheterization may help in preventing injuries in high risk cases, but it may not be easy in cases like in big myomas. Side effects like lower backache and hematuria occur frequently in most patients.…”
Section: Discussionmentioning
confidence: 99%
“…4 Another interesting case report by Vetere et al demonstrated the versatility of HS to do a salpingo-oophorectomy of a complex ovarian mass on one side but it caused a ureteral fistula while doing salpingo-oophorectomy on the normal side in the same patient. 5 HS related ureteral injuries are usually energy induced or by devascularization. It can lead to ureterovaginal fistulas or strictures in the lower 1/3rd of ureter.…”
Section: Discussionmentioning
confidence: 99%